ความสัมพันธ์ระว่างปัจจัยส่วนบุคคล ความฉลาดทางอารมณ์ สภาพแวดล้อมในการทำงานและภาวะผู้นำการปรับเปลี่ยนของหัวหน้าหอผู้ป่วยโรงพยาบาลเอกชน เขตกรุงเทพมหานคร - กาญจนา ธานะ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purposes of this research were to study adaptive leadership of head nurses, to examine the relationships between personal factors, emotional intelligence, working environment and adaptive leadership, and to search for the variables which could predict adaptive leadership of head nurses. Subjects consisted of 229 head nurses, private hospitals, Bangkok Metropolis. Research instruments were personal factors, emotional intelligence, working environment, and adaptive leadership questionnaires which were tested for content validity by 6 experts. Cronbach’s alpha coefficient reliability were tested for reliability which were .89, .91, and .94 respectively. Data were analyzed by percentage, mean, standard deviation, contingency coefficient, Chi-square, Pearson’s product moment correlation coefficient, and stepwise multiple regression. Major findings were as follows: 1.The adaptive leadership of head nurses in private hospitals, Bangkok Metropolis was high level ([Mean] = 4.09, SD = .43). 2.Personal factors of head nurses in term of education level was positive significantly related to adaptive leadership, at the 0.05 level (C = .19). Experience and administration training were not significantly related to adaptive leadership of head nurses in private hospitals, Bangkok metropolis. 3.Emotional intelligence and working environment were positive significantly related to adaptive leadership of head nurses in private hospitals, Bangkok Metropolis at the 0.05 level (r = .57 and .60 respectively).4. Variables that could predict adaptive leadership of head nurses at .05 level were emotional intelligence and working environment. These predictors accounted for 50.9 percents of variance. The standardize formula derived from the analysis was as follow: Z [subscript adaptive .leadership] = .600 Z[subscript working environment] + .591 Z[subscript emotional intelligence]